Effect of anti-digoxin antiserum on endoxin and membrane ATPase activity in hypoxia-reoxygenation induced myocardial injury - Ke Yong-Sheng; Liu Zhao-Fang; Yang Hao; Yang Ting; Huang Jia-Sheng; Rui Shi-Bao; Cheng Guang-Hua; Wang You-Xia (Acta Pharmacologica Sinica, 2016)
"AIM: To evaluate the protective effect of anti-digoxin antiserum on hypoxia-reoxygenation induced injured myocardium and its mechanism. METHODS: Anti-digoxin antiserum of different concentrations was used, its effect on endoxin and ATPase activity in cell membrane in hypoxia-reoxygenation myocardium model was observed. RESULTS: The level of endoxin was remarkably higher, ATPase activities in cell membrane were remarkably lower in hypoxic group and hypoxia-reoxygenation injury group than those of normal group; anti-digoxin antiserum could resume ATPase activity in a concentration-dependent manner. CONCLUSION: Rise of endoxin was the molecular biological basis of myocardial damage during myocardial hypoxia-reoxygenation. Anti-digoxin antiserum had lessened myocardial injury and had a protective effect on hypoxia-reoxygenation myocardium by antagonizing effect of endoxin."